A survey of the benefits and issues arising from the deployment of physical artefacts in computer science teaching - E. Currie; C. James-Reynolds (European Alliance for Innovation (EAI), 2017)
This paper describes the introduction of the use of physical artefacts in the teaching of the curriculum in the Department of Computer Science at Middlesex University. The rationale for the change is discussed, together with a description of the various technologies and the areas in which they were deployed. We conclude with a discussion of the outcomes of the work and the conclusions reached, prime amongst which are that the policy has been successful in motivating and engaging students, with a resultant improvement in student progression. In addition to their value in the taught part of the curriculum, these technologies have enabled students to become involved in real-world projects, interacting with external organizations and producing products of value in diverse areas such as the arts and assistive technologies.